Hypothermia Treatment for Neonatal Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs)
Treatment with mild whole body hypothermia after birth asphyxia was evaluated in 10 of 16 newborns with EEG burst suppression evidence of a bad prognosis, followed at the Imperial College School of Medicine, London, UK.